Socrates’ kατάβασις and the Sophistic Shades: Education and Democracy - Christine Rojcewicz (Plato, 2023)
This article addresses the unusually elaborate dramatic context in Plato’s Protagoras and effect of sophistry on democratic Athens. Because Socrates evokes Odysseus’ κατάβασις in the Odyssey to describe the sophists in Callias’ house (314c-316b), I propose that Socrates depicts the sophists as bodiless shades residing in Hades. Like the shades dwelling in Hades with no connection to embodied humans on Earth, the sophists in the Protagoras are non-Athenians with no consideration for the democratic body of the Athenian πόλις. I conclude that sophistry can be detrimental to Athenian democracy because it can produce education inequality founded on wealth inequality.